Je Cherche Fortune: Identity, Counterculture, and Profit in Fin-de-siècle Montmartre - Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2004)
This paper examines the Parisian neighbourhood of Montmartre during the 1880s and 1890s. Isolating themselves on a hilltop to the north of the city, a defiant community of painters and poets left the busy macadam below to position themselves physically and symbolically at the apex of anti-bourgeois, countercultural sentiment. Known for its subversive character, Montmartre's legacy appealed to these passionate and creative youths, and their appropriation of a semi-rural district on the fringes of the metropolitan centre of modernity symbolized their desire to escape stifling cultural traditions. Particularly revealing are the ways in which their art and literature represented at once a deeply interior questioning of identity as well as a loosely unified movement of cultural protest. By the turn of the 20th century, many of these artists and writers had been tamed by the commercialization of their nonconformity, but Montmartre remains a powerful site for the memory of its influential social and cultural transgressions.